2002
DOI: 10.1104/pp.011018
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Visualization of Peroxisomes and Cytoskeletal Elements Reveals Actin and Not Microtubule-Based Peroxisome Motility in Plants,

Abstract: Peroxisomes were visualized in living plant cells using a yellow fluorescent protein tagged with a peroxisomal targeting signal consisting of the SKL motif. Simultaneous visualization of peroxisomes and microfilaments/microtubules was accomplished in onion (Allium cepa) epidermal cells transiently expressing the yellow fluorescent protein-peroxi construct, a green fluorescent protein-mTalin construct that labels filamentous-actin filaments, and a green fluorescent proteinmicrotubule-binding domain construct th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
159
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(172 citation statements)
references
References 64 publications
(63 reference statements)
11
159
0
Order By: Relevance
“…The latter was frequently associated with the formation of peroxisome aggregates ( Fig. 2D; Supplemental Video S4), which is consistent with previously reported effects on organelle motility by pharmacological actin cytoskeleton interference (Mathur et al, 2002). Despite this drastic perturbation of organelle motility and actin cytoskeleton architecture, affected cells remained alive because individual peroxisomes still exhibited few saltatory movements (Supplemental Video S4).…”
Section: Genetic Interference With Actin Cytoskeleton Function As a Nsupporting
confidence: 78%
See 1 more Smart Citation
“…The latter was frequently associated with the formation of peroxisome aggregates ( Fig. 2D; Supplemental Video S4), which is consistent with previously reported effects on organelle motility by pharmacological actin cytoskeleton interference (Mathur et al, 2002). Despite this drastic perturbation of organelle motility and actin cytoskeleton architecture, affected cells remained alive because individual peroxisomes still exhibited few saltatory movements (Supplemental Video S4).…”
Section: Genetic Interference With Actin Cytoskeleton Function As a Nsupporting
confidence: 78%
“…and Chua, 2002;Mano et al, 2002;Mathur et al, 2002). We expressed a GFP variant with a C-terminal peroxisomal targeting sequence (GFP-PTS1; see ''Materials and Methods'') with or without HvADF3 in barley leaf epidermal cells and studied peroxisomal movement by epifluorescence microscopy at 60 h after particle bombardment.…”
Section: Genetic Interference With Actin Cytoskeleton Function As a Nmentioning
confidence: 99%
“…This apparent stickiness of mitochondria in the absence of their actin scaffold is not observed with other organelles that move on actin. For example, while peroxisomes and Golgi bodies move on actin and latrunculin B arrests this movement, neither organelle forms large clusters in response to actin depolymerization (Nebenführ et al, 1999;Brandizzi et al, 2002;Mano et al, 2002;Mathur et al, 2002;Sparkes et al, 2008). Furthermore, the clustering of mitochondria in friendly is not due to a general cytoskeletal or motor defect, since the distribution and movement of peroxisomes are not affected in the mutant (Supplemental Fig.…”
Section: Clusters In the Friendly Mutant Are Composed Of Discrete Orgmentioning
confidence: 99%
“…As well as arising from the ER, peroxisomes can proliferate, divide and be partitioned between daughter cells during division (Motley and Hettema, 2007;Fagarasanu et al, 2009). Peroxisomes are dynamic organelles which move on the actin-myosin system in plants (Mathur et al, 2002) and yeast (Fagarasanu et al, 2009), and on microtubules in mammals (Schrader et al, 2000). Consistent with the ability to be derived from the ER membrane, peroxisomes appear to have been an 'invention' of eukaryotic cells (Schluter et al, 2006) and are found in almost all eukaryotes.…”
Section: Introductionmentioning
confidence: 99%